Autophagy and LRRK2 in the Aging Brain - Albanese, Federica; Novello, Salvatore; Morari, Michele (Frontiers in Neuroscience, 2019)
Autophagy is a highly conserved process by which long-lived macromolecules, protein aggregates and dysfunctional/damaged organelles are delivered to lysosomes for degradation. Autophagy plays a crucial role in regulating protein quality control and cell homeostasis in response to energetic needs and environmental challenges. Indeed, activation of autophagy increases the life-span of living organisms, and impairment of autophagy is associated with several human disorders, among which neurodegenerative disorders of aging, such as Parkinson’s disease. These disorders are characterized by the accumulation of aggregates of aberrant or misfolded proteins that are toxic for neurons. Since aging is associated with impaired autophagy, autophagy inducers have been viewed as a strategy to counteract the age-related physiological decline in brain functions and emergence of neurodegenerative disorders. Parkinson’s disease is a hypokinetic, multisystemic disorder characterized by age-related, progressive degeneration of central and peripheral neuronal populations, associated with intraneuronal accumulation of proteinaceous aggregates mainly composed by the presynaptic protein α-synuclein. α-synuclein is a substrate of macroautophagy and chaperone-mediated autophagy (two major forms of autophagy), thus impairment of its clearance might favor the process of α-synuclein seeding and spreading that trigger and sustain the progression of this disorder. Genetic factors causing Parkinson’s disease have been identified, among which mutations in the LRRK2 gene, which encodes for a multidomain protein encompassing central GTPase and kinase domains, surrounded by protein-protein interaction domains. Six LRRK2 mutations have been pathogenically linked to Parkinson’s disease, the most frequent being the G2019S in the kinase domain. LRRK2-associated Parkinson’s disease is clinically and neuropathologically similar to idiopathic Parkinson’s disease, also showing age-dependency and incomplete penetrance. Several mechanisms have been proposed through which LRRK2 mutations can lead to Parkinson’s disease. The present article will focus on the evidence that LRRK2 and its mutants are associated with autophagy dysregulation. Studies in cell lines and neurons in vitro and in LRRK2 knock-out, knock-in, kinase-dead and transgenic animals in vivo will be reviewed. The role of aging in LRRK2-induced synucleinopathy will be discussed. Possible mechanisms underlying the LRRK2-mediated control over autophagy will be analyzed, and the contribution of autophagy dysregulation to the neurotoxic actions of LRRK2 will be examined.